Aryl hydrocarbon receptor and unexplained miscarriage. Issue 6 (15th May 2017) - Fan, Hongjie; Su, Xiaoling; Yang, Binlie; Zhao, Aimin
Abstract: Aim: The aim of this study was to carry out a preliminary investigation of the expression of aryl hydrocarbon receptor (AhR) in decidua and villus and the relationship between AhR and unexplained miscarriage. Methods: The expression of AhR mRNA and protein from decidua and villus were measured using real‐time reverse transcription–polymerase chain reaction, western blot and immunohistochemistry in 34 patients with unexplained miscarriage (miscarriage group) and 38 women with normal early pregnancy (control group). Results: The AhR mRNA and protein expression was increased significantly in the villus in both groups compared with decidua ( P < 0.05, P < 0.05). In decidua, AhR mRNA and protein expression in the miscarriage group was increased significantly compared with the control group ( P < 0.05, P < 0.05). In villus, AhR mRNA and protein expression in the miscarriage group was increased significantly compared with the control group ( P < 0.05, P < 0.05). AhR is expressed mostly in the cytoplasm of syncytiotrophoblasts in villus, and also in the cytoplasm of decidual cells. Conclusions: AhR was expressed more in the villus than in the decidua, and the upregulation of AhR mRNA and protein expression is associated with the pathogenesis of unexplained miscarriage.